Navigating uncertainty and competing objectives: Spring chinook salmon recovery in the upper Willamette river - Claire E. Couch; J. Rose Wallick; James T. Peterson; Bailey A. Morgan; Matthew L. Keefer; Christopher C. Caudill; Kathleen G. O’Malley; Christina A. Murphy; James S. White; Jake R. Kelley; Dalton J. Hance; Gabriel S. Hansen; et al. (Reviews in Fish Biology and Fisheries, 2026)

Impacts of Quaternary Climate History on the Biogeography of Specialized Butterflies in the Great Basin of North America - Sarah B. Bialik; Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; James A. Fordyce; Katherine L. Bell; Matthew L. Forister; Chris C. Nice (Journal of Biogeography, 2026)
Aim Dramatic Quaternary climate fluctuations impacted the evolutionary history and contemporary biogeography of many residents of the Great Basin Desert of western North America. This study investigates the historical biogeographic processes that shaped the contemporary distribution of genetic variation in a polytypic group of specialized butterflies that are residents of unique dune and playa habitats. Many of the subspecies are considered to be threatened and this study uses high‐resolution SNP data to understand their history and quantify patterns of differentiation to inform conservation. Location Great Basin, western North America. Taxon The pallid dotted blue butterfly complex ( Euphilotes pallescens , Lycaenidae). Methods We constructed reduced‐representation genomic libraries to generate population genomics data that were used in clustering, ordination, and phylogenetic analyses. Pairwise differentiation between localities was quantified and the relationship between genomic differentiation and geography was analysed using a linear model. In addition, an estimated effective migration surface illustrated geographic patterns of genomic variation. Results Euphilotes pallescens populations were clearly differentiated from congeneric species and several subspecies, especially in the northwestern portion of the sampled range, were identifiable from genomic variation. When geographic distance was controlled, genetic differentiation was greatest between populations of Eu. pallescens compared to congeners, and within Eu. pallescens , northwestern populations were more differentiated than southern populations. The estimated effective migration surface also showed greater areas of reduced gene flow in the northwestern region. Main Conclusions Euphilotes pallescens comprises isolated populations on dune habitats in the Great Basin. Populations in the northwestern region are especially isolated and their patterns of genetic variation are consistent with the history of climate change and ancient pluvial lakes that occupied much of this region at intervals during the Quaternary. These butterflies are members of unique, localized communities whose persistence requires protections from anthropogenic threats, especially habitat loss including from recreation and off‐road vehicles in sensitive habitats.

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Plaice (Pleuronectes platessa) survivability in a Celtic Sea bottom-seine fishery: A phased approach - Martin Oliver; Matthew McHugh; Shane Murphy; Cóilín Minto; Thomas Noack; Ronán Cosgrove (Fisheries Research, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Correction: Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2026)

Biogeography and hidden diversity in the coffee snake species complex Ninia atrata (Dipsadinae) from South America and the Lesser Antilles - Michael J. Jowers; Oriana C. Dempster Ortigoza; Teddy Angarita-Sierra; John C. Murphy; AmaËl Borzée; Gilson A. Rivas; Richard M. Lehtinen; Matthew J. Ingrasci; Eric N. Smith (Systematics and Biodiversity, 2025)

Recent Chemo-morphological coma evolution of comet 67P/Churyumov–Gerasimenko - Brian P. Murphy; Cyrielle Opitom; Colin Snodgrass; Sophie E. Deam; Léa Ferellec; Matthew Knight; Vincent Okoth; Bin Yang (Planetary and Space Science, 2025)

Mid‐Holocene drying of K'gari lakes (subtropical eastern Australia) necessitates re‐evaluation of the El Niño–Southern Oscillation climate links and future drying risk - John Tibby; Haidee Cadd; Matthew Harris; Jonathan C. Marshall; Jonathan Tyler; Cameron Barr; Francesca McInerney; Patrick Moss; Claire Murphy; Patricia S. Gadd; Geraldine E. Jacobsen; Mathew Raven; et al. (Journal of Quaternary Science, 2025)
The Holocene history of Australia's climate is surprisingly poorly understood. This is, in part, because of the relatively weak forcing of Holocene climate versus that of the late Pleistocene. However, it is commonly suggested that eastern Australia dried during the mid‐ to late‐Holocene and that this was in response to increased activity in the El Niño–Southern Oscillation (ENSO), in particular, the intensification of the El Niño phase of ENSO. While this has been inferred from numerous locations, data from K'gari (a subtropical sand island adjacent to the east coast) was amongst the first used to develop this hypothesis and features heavily in the discussion of ENSO intensification. This study examines published and new data from three ≥4.5 m deep K'gari lakes that demonstrate a strong drying event during the middle Holocene (from 7640 to 5600 cal a BP), followed by a wetter late Holocene climate. This contrasts somewhat with previous arguments about K'gari's history that suggest a late Holocene drying. In turn, this indicates a need to re‐evaluate the notion that ENSO intensification drove late‐Holocene drying in the region. It also indicates that even large, deep lakes on K'gari, which are iconic landmarks with substantial cultural, ecological and economic values, are vulnerable to drying.

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Disentangling global geochemical signals from local diagenetic alteration in shallow-water marine carbonates during OAE1a - Matthew D. Nadeau; Jack G. Murphy; Cedric J. Hagen; Ziman Wu; Alliya A. Akhtar; Anne-Sofie Ahm; Daniel A. Stolper; Adam C. Maloof; John A. Higgins (Earth and Planetary Science Letters, 2025)

Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2025)
The climate of the Maritime Continent, including Singapore, is influenced by a wide range of tropical drivers including the El-Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Madden–Julian Oscillation (MJO), and equatorial wave activity. In Singapore, the rainfall pattern is often marked by episodes of short intense rainfall bursts, primarily driven by mesoscale convective systems, such as Sumatra squall lines. These episodes often result in local flash floods and strong wind bursts. Here we analyse 33 years of Sumatra squalls affecting Singapore and investigate the potential impact of the main modes of climate variability and atmospheric equatorial tropical waves. Highlighted results are that, on average, Sumatra squalls originate from Sumatra and the Strait of Malacca, make landfall over Singapore primarily in the morning and last about 2 h, and are more frequent from April to November. These squalls tend to be more frequent under La Niña conditions, which are associated with locally warm sea surface temperature anomalies and favourable atmospheric anomalies over the Maritime Continent region. On intraseasonal scale, the MJO may play a role in setting the westerlies and enhancing convective conditions favorable for the squalls to intensify and propagate eastward. Convectively-coupled Kelvin waves are important for the initiation and eastward propagation of the squalls over Sumatra and the Strait of Malacca, while equatorial Rossby, and mixed Rossby gravity waves influence their meridional propagation toward Singapore.

Profiling Inter‐Specific and Inter‐Estuarine Variation in Per‐ and Polyfluoroalkyl Substances Across Two Recreational Fishing Havens - Matthew D. Taylor; Julian M. Hughes; Jeff Murphy; Faith A. Ochwada‐Doyle (Fisheries Management and Ecology, 2025)
Contamination of estuaries with per‐ and polyfluoroalkyl substances (PFAS), such as perfluorooctane sulfonate (PFOS), may impact recreational fishers who consume their catch. However, the presence and concentration of PFAS across commonly harvested estuarine taxa is rarely quantified. We used data from a state‐wide survey of recreational fishers to design and conduct a sampling program for assessing PFAS contamination across two recreational fishing havens (Lake Macquarie and Botany Bay, New South Wales, Australia). Perfluorodecanoic acid (PFDA) and PFOS were the primary contaminants in edible tissues of recreationally harvested species, and concentrations were highly variable. In Lake Macquarie, all samples were below screening criteria, as were invertebrates in both estuaries. In Botany Bay, some fish exceeded screening criteria, but the most frequently harvested recreational species had the lowest concentrations of all fish across both estuaries. Ecological factors likely contributed to substantial variation in PFAS accumulation levels among different recreational species. Recreational fisheries surveys provide a solid foundation to frame investigations of exposure risk and support the development of spatially tailored dietary advice.

Survivability of spurdog (Squalus acanthias) in an inshore otter trawl fishery - Martin Oliver; Ross O’Neill; Matthew McHugh; Daragh Browne; Shane Murphy; Cóilín Minto; Nicolas Chopin; Ronán Cosgrove (Fisheries Research, 2025)

Variable post-capture condition estimated by visual assessment for key recreational species discarded in a nearshore marine charter fishery off eastern Australia - Julian M. Hughes; Daniel D. Johnson; Faith A. Ochwada-Doyle; Jeffrey J. Murphy; Matthew D. Taylor; Ashley M. Fowler (Fisheries Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Integrating organic fertilizers in maize-mung bean intercropping: implications for soil carbon dynamics and greenhouse gas reduction - Morad Mirzaei; Matthew Saunders; Rachael Murphy; Karl Richards; Seyed Mohammad Nasir Mousavi; Fateme Aghamir; Ján Horák; Roberto Mancinelli; Yuan Li; Emanuele Radicetti (Nutrient Cycling in Agroecosystems, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Cholesterol-loaded cyclodextrin improves motility and survival of cryopreserved zebrafish (Danio rerio) sperm - Jennifer L. Matthews; Joy M. Murphy; Zoltan M. Varga (Cryobiology, 2024)

Spatially explicit models reveal rodents rapidly colonize soybean fields regardless of pre-planting chemical treatment timing for cover crop removal - Jena L. Nierman; Sean M. Murphy; Wendy Leuenberger; Allison G. Davis; John J. Cox; Matthew T. Springer (Crop Protection, 2024)

Pulsatile Ventilation Flow in Polychaete Alitta succinea Burrows - Elizabeth A. K. Murphy; Matthew A. Reidenbach (Journal of Marine Science and Engineering, 2024)
In aquatic sediments, active ventilation of burrows is an important component of sediment metabolism, transporting solutes across the sediment–water interface. Within a burrow, the temporal and spatial structure of the flow velocity can dictate the flux of solutes across the burrow walls. However, it is difficult to measure the fine-scale flow dynamics within a burrow due to the opacity of marine sediments. Here, we allowed a nereid polychaete Alitta succinea, a cosmopolitan deposit feeder found in brackish to marine soft sediments, to construct burrows in a transparent, elastic sediment analog. This allowed the measurement of the temporal velocity structure of flow in the burrow using particle tracking velocimetry. We find that the flow within the burrow of this piston-pumping polychaete is unsteady and that oscillations in flow velocity are damped with distance along the tube. We also show that the flow velocity in a tube scales with worm size. Conversely, neither the unsteadiness of flow oscillations nor the stroke frequency of the worm pump scale with worm size.

Parsing the toxicity paradox: Composition and duration of exposure alter predicted oil spill effects by orders of magnitude - Deborah P. French-McCay; Hilary J. Robinson; Julie E. Adams; Matthew A. Frediani; Matthew J. Murphy; Cheryl Morse; Melissa Gloekler; Thomas F. Parkerton (Marine Pollution Bulletin, 2024)

Survivorship of discarded cuckoo ray in bottom trawl fisheries in the northern Bay of Biscay, Southern Celtic and Irish Seas - Loïc Baulier; Matthew McHugh; Cóilín Minto; Fabien Morandeau; Shane Murphy; Quiterie Sourget; Martin Oliver; Marie Morfin (Fisheries Research, 2024)

Economic potential of agricultural-riparian shrub willow: An evaluation of the biomass producing capabilities and costs of cultivating Salix viminalis downslope of potato cropping systems in PEI - Holly D.M. Wilts; David L. Burton; Aitazaz A. Farooque; William R. Schroeder; Brian Murray; Emily K. Murphy; Matthew Ramsay (Biomass and Bioenergy, 2024)

Modelling count data with partial differential equation models in biology - Matthew J. Simpson; Ryan J. Murphy; Oliver J. Maclaren (Journal of Theoretical Biology, 2024)

Characterization of nanoparticles in silicon dioxide food additive - Sadia Afrin Khan; Monique E. Johnson; Matthew S. Kalan; Antonio R. Montoro Bustos; Savelas A. Rabb; Ingo H. Strenge; Karen E. Murphy; Timothy R. Croley (Food Additives & Contaminants: Part A, 2024)

Reproductive biology of male common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2023)
Reproductive parameters were assessed in 64 male common dolphins ( Delphinus delphis ) examined post-mortem from strandings and bycatch in New Zealand between 1999 and 2020. The stages of male sexual maturation were assessed using morphological measurements and histological examination of testicular tissue. Age was determined via growth layer groups (GLGs) in teeth. The average age (ASM) and length (LSM) at attainment of sexual maturity were estimated to be 8.8 years and 198.3 cm, respectively. Individual variation in ASM (7.5–10 years) and LSM (190–220 cm) was observed in New Zealand common dolphins. However, on average, sexual maturity was attained at a similar length but at a marginally younger age (< 1 year) in New Zealand compared to populations in the Northern Hemisphere. All testicular variables proved better predictors of sexual maturity compared to demographic variables (age and total body length), with combined testes weight the best outright predictor of sexual maturity. Reproductive seasonality was observed in male common dolphins, with a significant increase in combined testes weight in austral summer. This aligns with most other studied populations, where seasonality in reproduction is typically observed. Given the known anthropogenic impacts on New Zealand common dolphins, we recommend that these findings be used as a baseline from which to monitor population-level changes as part of conservation management efforts.

Assessment of cod survival in the Irish fly-shoot seine fishery using survivorship pop-up satellite archival tags - Martin Oliver; Ross O’Neill; Matthew McHugh; Daragh Browne; Shane Murphy; Cóilín Minto; Ronán Cosgrove (Fisheries Research, 2023)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - Matthew Bluett-Duncan; Denise Astill; Rana Charbak; Jill Clayton-Smith; Susan Cole; Penny A. Cook; Jo Cozens; Karen Keely; Jacki Morris; Raja Mukherjee; Emma Murphy; Peter Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Spatial and temporal scaling of sub-daily extreme rainfall for data sparse places - R. L. Wilby; C. W. Dawson; D. Yu; Z. Herring; A. Baruch; M. J. Ascott; D. L. Finney; D. M. J. Macdonald; J. H. Marsham; T. Matthews; C. Murphy (Climate Dynamics, 2023)
Global efforts to upgrade water, drainage, and sanitation services are hampered by hydrometeorological data-scarcity plus uncertainty about climate change. Intensity–duration–frequency (IDF) tables are used routinely to design water infrastructure so offer an entry point for adapting engineering standards. This paper begins with a novel procedure for guiding downscaling predictor variable selection for heavy rainfall simulation using media reports of pluvial flooding. We then present a three-step workflow to: (1) spatially downscale daily rainfall from grid-to-point resolutions; (2) temporally scale from daily series to sub-daily extreme rainfalls and; (3) test methods of temporal scaling of extreme rainfalls within Regional Climate Model (RCM) simulations under changed climate conditions. Critically, we compare the methods of moments and of parameters for temporal scaling annual maximum series of daily rainfall into sub-daily extreme rainfalls, whilst accounting for rainfall intermittency. The methods are applied to Kampala, Uganda and Kisumu, Kenya using the Statistical Downscaling Model (SDSM), two RCM simulations covering East Africa (CP4 and P25), and in hybrid form (RCM-SDSM). We demonstrate that Gumbel parameters (and IDF tables) can be reliably scaled to durations of 3 h within observations and RCMs. Our hybrid RCM-SDSM scaling reduces errors in IDF estimates for the present climate when compared with direct RCM output. Credible parameter scaling relationships are also found within RCM simulations under changed climate conditions. We then discuss the practical aspects of applying such workflows to other city-regions.

Relating drought indices to impacts reported in newspaper articles - Paul O'Connor; Conor Murphy; Tom Matthews; Robert L. Wilby (International Journal of Climatology, 2023)
Relating drought indicators and real‐world impacts is fundamental for understanding and addressing drought vulnerability. We link drought indices and impacts from newspapers compiled in the Irish Drought Impacts Database (IDID) for the period 1900–2016. For three catchment clusters across the island of Ireland we link the Standardized Precipitation Index (SPI) with land‐based impacts and the Standardized Streamflow Index (SSI) with water‐based impacts by matching total reported articles per month with concurrent drought indices. Using logistic regression we find SPI‐3 links best with land‐based impact reports, whereas SSI‐2 links best with water‐based impact reports. Catchments in the east/southeast display the highest sensitivity to land‐ and water‐based impacts; however, in summer months at low deficits northwestern catchments show a higher likelihood of impact reports. In winter months the likelihood of water‐based impacts is considerably greater than the land‐based equivalent, particularly in east/southeastern catchments. Moreover, the likelihood of news‐worthy drought impacts has changed over the 117 year period. More severe deficits are required to induce a high likelihood (0.6) of land‐ and water‐based impacts in east/southeastern and southwestern catchments during 1961–2016 compared with 1900–1960. Largest changes emerge in the southwest with SPI‐3 values of −2.51 (

Evaluation of a marine mammal status and trends contaminants indicator for European waters - Rosie S. Williams; Andrew Brownlow; Andrew Baillie; Jonathan L. Barber; James Barnett; Nicholas J. Davison; Robert Deaville; Mariel ten Doeschate; Rod Penrose; Matthew Perkins; Ruth Williams; Paul D. Jepson; et al. (Science of The Total Environment, 2023)

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Reproductive biology of female common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2022)
Reproductive biology was assessed in 106 female common dolphins ( Delphinus delphis ) examined post-mortem from stranding and bycatch events along the New Zealand coastline between 1997 and 2019. The average age (ASM) and length (LSM) at sexual maturity was estimated at 7.5 years and 183.5 cm, respectively. The total number of corpora in mature individuals increased with age and appeared to persist throughout life. Ovarian asymmetry was apparent, with the left ovary displaying higher rates of ovulation, and a maximum of 19 corpora recorded for a 24-year-old female. The estimated ovulation and annual pregnancy rates for mature females were 0.39 year −1 and 30%, respectively. Conception and calving occurred year-round, with a weak seasonal increase observed in late austral spring and early austral summer. As these data did not clearly show whether seasonality was present, the gestation, lactation, and resting periods were calculated as either 12.6 or 12.8 months based on the presence/absence of seasonality, respectively. Similarly, calving interval ranged from 3.15 to 3.2 years, depending upon whether seasonality was considered. The estimated LSM of the New Zealand population aligns with other populations globally, although the estimated ASM is younger by approximately 6 months. Other reproductive parameters align with Northern Hemisphere populations, although demonstrate variation, which may reflect adaptations to local conditions such as water temperature and prey availability. As the species is subject to anthropogenic impacts including pollution and bycatch, we suggest our findings be used as a baseline with which to monitor trends in population parameters.

Persistence and expansion of cryptic endangered red wolf genomic ancestry along the American Gulf coast - Bridgett M. vonHoldt; Kristin E. Brzeski; Matthew L. Aardema; Christopher J. Schell; Linda Y. Rutledge; Steven R. Fain; Amy C. Shutt; Anna Linderholm; William J. Murphy (Molecular Ecology, 2022)
Admixture and introgression play a critical role in adaptation and genetic rescue that has only recently gained a deeper appreciation. Here, we explored the geographical and genomic landscape of cryptic ancestry of the endangered red wolf that persists within the genome of a ubiquitous sister taxon, the coyote, all while the red wolf has been extinct in the wild since the early 1980s. We assessed admixture across 120,621 single nucleotiode polymorphism (SNP) loci genotyped in 293 canid genomes. We found support for increased red wolf ancestry along a west‐to‐east gradient across the southern United States associated with historical admixture in the past 100 years. Southwestern Louisiana and southeastern Texas, the geographical zone where the last red wolves were known prior to extinction in the wild, contained the highest and oldest levels of red wolf ancestry. Further, given the paucity of inferences based on chromosome types, we compared patterns of ancestry on the X chromosome and autosomes. We additionally aimed to explore the relationship between admixture timing and recombination rate variation to investigate gene flow events. We found that X‐linked regions of low recombination rates were depleted of introgression, relative to the autosomes, consistent with the large X effect and enrichment with loci involved in maintaining reproductive isolation. Recombination rate was positively correlated with red wolf ancestry across coyote genomes, consistent with theoretical predictions. The geographical and genomic extent of cryptic red wolf ancestry can provide novel genomic resources for recovery plans targeting the conservation of the endangered red wolf.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Historical droughts in Irish catchments 1767–2016 - Paul O'Connor; Conor Murphy; Tom Matthews; Robert L. Wilby (International Journal of Climatology, 2022)
Recent prolonged dry periods in summer 2018 and spring 2020 have reawakened interest in drought in Ireland, prompting questions regarding historical drought occurrence and potential long‐term risks. Employing 250 years of monthly precipitation and flow reconstructions, we investigate historical drought in Irish catchments evaluating the characteristics (number of events, duration, and deficits) of moderate, severe, and extreme droughts as well as the propagation of meteorological to hydrological drought. Using standardized indices, we identify three distinct catchment types. Cluster 1 catchments, located in the wetter northwest are characterized by small areas, low groundwater storage, and the highest frequency of hydrological drought relative to other catchments. Cluster 3 catchments, located in the drier east and southeast have larger areas, greater groundwater storage, the highest frequency of meteorological drought but the least hydrological droughts. However, once established, droughts in Cluster 3 tend to be more persistent with large accumulated deficits. Cluster 2 catchments, located in the southwest and west, are intermediate to Clusters 1 and 3, with hydrological droughts typically of shorter durations, reduced accumulated deficits but greater mean deficits. The most extreme droughts based on accumulated deficits across all catchments occurred in 1803–1806, 1854–1859, 1933–1935, 1944–1945, 1953–1954, and 1975–1977. Although not as severe, droughts in 1887–1888, 1891–1894, and 1971–1974 also appear as significant extremes. Changes in drought characteristics reveal a complex picture with the direction, magnitude, and significance of trends dependent on the accumulation period used to define drought, the period of record analysed, and the reference period used to standardize indices. Of particular note is a tendency towards shorter, more intense meteorological and hydrological droughts. Our findings offer important insight for drought and water management in Ireland given the paucity of extreme droughts in short observed river flow records.

Dynamical–statistical seasonal forecasts of winter and summer precipitation for the Island of Ireland - Saeed Golian; Conor Murphy; Robert L. Wilby; Tom Matthews; Seán Donegan; Dáire Foran Quinn; Shaun Harrigan (International Journal of Climatology, 2022)
Seasonal precipitation forecasting is highly challenging for the northwest fringes of Europe due to complex dynamical drivers. Hybrid dynamical–statistical approaches offer potential to improve forecast skill. Here, hindcasts of mean sea level pressure (MSLP) from two dynamical systems (GloSea5 and SEAS5) are used to derive two distinct sets of indices for forecasting winter (DJF) and summer (JJA) precipitation over lead‐times of 1–4 months. These indices provide predictors of seasonal precipitation via a multiple linear regression model (MLR) and an artificial neural network (ANN) applied to four Irish rainfall regions and the Island of Ireland. Forecast skill for each model, lead time, and region was evaluated using the correlation coefficient ( r ) and mean absolute error (MAE), benchmarked against (a) climatology, (b) bias corrected precipitation hindcasts from both GloSea5 and SEAS5, and (c) a zero‐order forecast based on rainfall persistence. The MLR and ANN models produced skilful precipitation forecasts with leads of up to 4 months. In all tests, our hybrid method based on MSLP indices outperformed the three benchmarks (i.e., climatology, bias corrected, and persistence). With correlation coefficients ranging between 0.38 and 0.81 in winter, and between 0.24 and 0.78 in summer, the ANN model outperformed MLR in both seasons in most regions and lead‐times. Forecast skill for summer was comparable to that in winter and for some regions/lead times even superior. Our results also show that climatology and persistence performed better than direct use of bias corrected dynamical outputs in most regions and lead‐times in terms of MAE. We conclude that the hybrid dynamical–statistical approach developed here—by leveraging useful information about MSLP from dynamical systems—enables more skilful seasonal precipitation forecasts for Ireland, and possibly other locations in western Europe, in both winter and summer.

Boundary layer hydrodynamics of patchy biofilms - Elizabeth A. K. Murphy; Julio M. Barros; Michael P. Schultz; Karen A. Flack; Cecily N. Steppe; Matthew A. Reidenbach (Biofouling, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Metabolism in the Midwest: research from the Midwest Aging Consortium at the 49th Annual Meeting of the American Aging Association - Michaela E. Murphy; Akilavalli Narasimhan; Alexis Adrian; Ankur Kumar; Cara L. Green; Carolina Soto-Palma; Chathurika Henpita; Christina Camell; Christopher S. Morrow; Chung-Yang Yeh; Claire E. Richardson; Cristal M. Hill; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Benchmarking seasonal forecasting skill using river flow persistence in Irish catchments - Dáire Foran Quinn; Conor Murphy; Robert L. Wilby; Tom Matthews; Ciaran Broderick; Saeed Golian; Seán Donegan; Shaun Harrigan (Hydrological Sciences Journal, 2021)

Spatio-Temporal Variability of Harbor Porpoise Life History Parameters in the North-East Atlantic - Sinéad Murphy; Marie A. C. Petitguyot; Paul D. Jepson; Rob Deaville; Christina Lockyer; James Barnett; Matthew Perkins; Rod Penrose; Nicholas J. Davison; Cóilín Minto (Frontiers in Marine Science, 2020)
Harbor porpoises exhibit early maturation, relatively short gestation/lactation periods and a faster rate of reproduction as compared to other cetacean species. Intrinsic and extrinsic factors can influence both population vital rates and population structure, which ultimately cause changes in dynamics within and between populations. Here, we undertook a retrospective analysis of mortality data collected over a 24-year period for assessing life history traits of the North-east Atlantic harbor porpoise population. We use time-period specific models for key life history relationships that considered cause of death of individuals (as a proxy for health status), sex and management unit (MU). Sexual variation in asymptotic length, asymptotic age, average length at 50% maturity (L50) and average age at 50% maturity (A50) were observed, with females attaining a larger asymptotic length, larger L50, and delaying attainment of both sexual and physical maturity, compared to males. While females are constrained in their minimum body size due to giving birth to proportionally larger offspring, males exhibited more plasticity in size at sexual maturity, enabling re-allocation of available energy resources toward reproduction. Data were then used to compare biological parameters among two porpoise MUs in United Kingdom waters, both of which in the current study exhibited reduced reproductive rates compared to other geographic regions. In both MUs, females significantly increased their A50 and males significantly declined in their L50. An increase in the age at asymptotic length was also observed in both sexes, along with a significant decline in the Gompertz growth rate parameter that was more apparent in the female data. While availability of suitable prey resources may be a limiting factor, a combination of other factors cannot be ruled out. Porpoises in the Celtic and Irish Seas MU were significantly larger in their maximum length, asymptotic length and L50 compared to porpoises in the North Sea MU throughout the study period, suggesting limited gene flow between these two MUs. These results justify the maintenance of these harbor porpoise MUs or assessment units, as two separate units, within the range of the North-east Atlantic population, and for indicator assessments under the EU’s Marine Strategy Framework Directive.

Multivariate Modelling of the Trace Element Chemistry of Arsenopyrite from Gold Deposits Using Higher-Dimensional Algebras - Sudharsan Thiruvengadam; Matthew Edmund Murphy; Jei Shian Tan; Roger John Watling; James Ian Stewart; Karol Miller (Mathematical Geosciences, 2020)

The forgotten drought of 1765–1768: Reconstructing and re‐evaluating historical droughts in the British and Irish Isles - Conor Murphy; Robert L. Wilby; Tom Matthews; Csaba Horvath; Arlene Crampsie; Francis Ludlow; Simon Noone; Jordan Brannigan; Jamie Hannaford; Robert McLeman; Eva Jobbova (International Journal of Climatology, 2020)
Historical precipitation records are fundamental for the management of water resources, yet rainfall observations typically span 100–150 years at most, with considerable uncertainties surrounding earlier records. Here, we analyse some of the longest available precipitation records globally, for England and Wales, Scotland and Ireland. To assess the credibility of these records and extend them further back in time, we statistically reconstruct (using independent predictors) monthly precipitation series representing these regions for the period 1748–2000. By applying the Standardized Precipitation Index at 12‐month accumulations (SPI‐12) to the observed and our reconstructed series we re‐evaluate historical meteorological droughts. We find strong agreement between observed and reconstructed drought chronologies in post‐1870 records, but divergence in earlier series due to biases in early precipitation observations. Hence, the 1800s decade was less drought prone in our reconstructions relative to observations. Overall, the drought of 1834–1836 was the most intense SPI‐12 event in our reconstruction for England and Wales. Newspaper accounts and documentary sources confirm the extent of impacts across England in particular. We also identify a major, “forgotten” drought in 1765–1768 that affected the British‐Irish Isles. This was the most intense event in our reconstructions for Ireland and Scotland, and ranks first for accumulated deficits across all three regional series. Moreover, the 1765–1768 event was also the most extreme multi‐year drought across all regional series when considering 36‐month accumulations (SPI‐36). Newspaper and other sources confirm the occurrence and major socio‐economic impact of this drought, such as major rivers like the Shannon being fordable by foot. Our results provide new insights into historical droughts across the British Irish Isles. Given the importance of historical droughts for stress‐testing the resilience of water resources, drought plans and supply systems, the forgotten drought of 1765–1768 offers perhaps the most extreme benchmark scenario in more than 250‐years.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Experimental Assessment of Two Non-Contrast MRI Sequences Used for Computational Fluid Dynamics: Investigation of Consistency Between Techniques - C. J. MacDonald; R. Hellmuth; L. Priba; E. Murphy; S. Gandy; S. Matthew; R. Ross; J. G. Houston (Cardiovascular Engineering and Technology, 2020)
Purpose Recent studies have noted a degree of variance between the geometries segmented by different groups from 3D medical images that are used in computational fluid dynamics (CFD) simulations of patient-specific cardiovascular systems. The aim of this study was to determine if the applied sequence of magnetic resonance imaging (MRI) also introduced observable variance in CFD results. Methods Using a series of phantoms MR images of vessels of known diameter were assessed for the time-of-flight and multi-echo data image combination sequences. Following this, patient images of arterio-venous fistulas were acquired using the same sequences. Comparisons of geometry were made using the phantom and patient images, and of wall shear stress quantities using the CFD results from the patient images. Results Phantom images showed deviations in diameter between 0 and 15% between the sequences, depending on vessel diameter. Patient images showed different geometrical features such as narrowings that were not present on both sequences. Distributions of wall shear stress (WSS) quantities differed from simulations between the geometries obtained from the sequences. Conclusion In conclusion, choosing different MRI sequences resulted in slightly different geometries of the same anatomy, which led to compounded errors in WSS quantities from CFD simulation.

Movement, habitat use, and survival of juvenile grass carp in an Appalachian reservoir - Matthew A. Weberg; Brian R. Murphy; John R. Copeland; Andrew L. Rypel (Environmental Biology of Fishes, 2020)

Reference points for predators will progress ecosystem‐based management of fisheries - Simeon L. Hill; Jefferson Hinke; Sophie Bertrand; Lowell Fritz; Robert W. Furness; James N. Ianelli; Matthew Murphy; Ricardo Oliveros‐Ramos; Lorien Pichegru; Rowland Sharp; Richard A. Stillman; Peter J. Wright; et al. (Fish and Fisheries, 2020)
Ecosystem‐based management of fisheries aims to allow sustainable use of fished stocks while keeping impacts upon ecosystems within safe ecological limits. Both the FAO Code of Conduct for Responsible Fisheries and the Aichi Biodiversity Targets promote these aims. We evaluate implementation of ecosystem‐based management in six case‐study fisheries in which potential indirect impacts upon bird or mammal predators of fished stocks are well publicized and well studied. In particular, we consider the components needed to enable management strategies to respond to information from predator monitoring. Although such information is available in all case‐studies, only one has a reference point defining safe ecological limits for predators and none has a method to adjust fishing activities in response to estimates of the state of the predator population. Reference points for predators have been developed outside the fisheries management context, but adoption by fisheries managers is hindered a lack of clarity about management objectives and uncertainty about how fishing affects predator dynamics. This also hinders the development of adjustment methods because these generally require information on the state of ecosystem variables relative to reference points. Nonetheless, most of the case‐studies include precautionary measures to limit impacts on predators. These measures are not used tactically and therefore risk excessive restrictions on sustainable use. Adoption of predator reference points to inform tactical adjustment of precautionary measures would be an appropriate next step towards ecosystem‐based management.

Multi‐century trends to wetter winters and drier summers in the England and Wales precipitation series explained by observational and sampling bias in early records - Conor Murphy; Robert L. Wilby; Tom K. R. Matthews; Peter Thorne; Ciaran Broderick; Rowan Fealy; Julia Hall; Shaun Harrigan; Phil Jones; Gerard McCarthy; Neil MacDonald; Simon Noone; et al. (International Journal of Climatology, 2020)
Globally, few precipitation records extend to the 18th century. The England Wales Precipitation (EWP) series is a notable exception with continuous monthly records from 1766. EWP has found widespread use across diverse fields of research including trend detection, evaluation of climate model simulations, as a proxy for mid‐latitude atmospheric circulation, a predictor in long‐term European gridded precipitation data sets, the assessment of drought and extremes, tree‐ring reconstructions and as a benchmark for other regional series. A key finding from EWP has been the multi‐centennial trends towards wetter winters and drier summers. We statistically reconstruct seasonal EWP using independent, quality‐assured temperature, pressure and circulation indices. Using a sleet and snow series for the UK derived by Profs. Gordon Manley and Elizabeth Shaw to examine winter reconstructions, we show that precipitation totals for pre‐1870 winters are likely biased low due to gauge under‐catch of snowfall and a higher incidence of snowfall during this period. When these factors are accounted for in our reconstructions, the observed trend to wetter winters in EWP is no longer evident. For summer, we find that pre‐1820 precipitation totals are too high, likely due to decreasing network density and less certain data at key stations. A significant trend to drier summers is not robustly present in our reconstructions of the EWP series. While our findings are more certain for winter than summer, we highlight (a) that extreme caution should be exercised when using EWP to make inferences about multi‐centennial trends, and; (b) that assessments of 18th and 19th Century winter precipitation should be aware of potential snow biases in early records. Our findings underline the importance of continual re‐appraisal of established long‐term climate data sets as new evidence becomes available. It is also likely that the identified biases in winter EWP have distorted many other long‐term European precipitation series.

Relative Importance of Landscape Versus Local Wetland Characteristics for Estimating Wetland Denitrification Potential - Marc Russell; Richard Fulford; Kate Murphy; Charles Lane; James Harvey; Darrin Dantin; Federico Alvarez; Janet Nestlerode; Aaron Teague; Matthew Harwell; Alejandro Almario (Wetlands, 2019)

Effect of γ-hydroxybutyrate (GHB) on driving as measured by a driving simulator - Evangelia Liakoni; Delia A. Dempsey; Matthew Meyers; Nancy G. Murphy; Dary Fiorentino; Christopher Havel; Christine Haller; Neal L. Benowitz (Psychopharmacology, 2018)

Roughness effects of diatomaceous slime fouling on turbulent boundary layer hydrodynamics - Elizabeth A. K. Murphy; Julio M. Barros; Michael P. Schultz; Karen A. Flack; Cecily N. Steppe; Matthew A. Reidenbach (Biofouling, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Toward a taxonomic definition of perennial wheat: a new species ×Tritipyrum aaseae described - Colin Curwen-McAdams; Matthew Arterburn; Kevin Murphy; Xiwen Cai; Stephen S. Jones (Genetic Resources and Crop Evolution, 2017)

Imaging in Vascular Access - Eoin A. Murphy; Rose A. Ross; Robert G. Jones; Stephen J. Gandy; Nicolas Aristokleous; Marco Salsano; Jonathan R. Weir-McCall; Shona Matthew; John Graeme Houston (Cardiovascular Engineering and Technology, 2017)

Erratum to: Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2017)

A 250‐year drought catalogue for the island of Ireland (1765–2015) - S. Noone; C. Broderick; C. Duffy; T. Matthews; R.L. Wilby; C. Murphy (International Journal of Climatology, 2017)
This work created a 250‐year historic drought catalogue by applying the Standardized Precipitation Index ( SPI ) to the Island of Ireland precipitation network (1850–2015) and a reconstructed precipitation series from 1765. Documentary sources from newspaper archives spanning the last 250 years, together with other historical sources are used to (1) add confidence to the quantitative detection of drought episodes and (2) gain insight to the socio‐economic impacts of historic droughts. The results show that Ireland is drought prone but recent decades are unrepresentative of the longer‐term drought climatology. A large decline in 30‐year accumulated SPI ‐12 values is evident from around the 1990s onwards. During the years 1850–2015 seven major drought rich periods were identified with an island‐wide fingerprint in 1854–1860, 1884–1896, 1904–1912, 1921–1923, 1932–1935, 1952–1954 and 1969–1977. These events exhibit substantial diversity in terms of drought development, severity and spatial occurrence. Two exceptionally long events are found in the record: the continuous drought of 1854–1860 and the drought of 1800–1809 (in fact a series of three droughts with brief interludes). Over the last 250 years, droughts have resulted in agricultural hardship, water resource crises and failures and preceded some of the major famines of the eighteenth and nineteenth centuries. This work shows that newspaper archives can be used to trace the progression of drought events and impacts and we thus advocate their wider use in corroborating quantitative assessments. The resulting catalogue challenges prevailing perceptions about drought in Ireland while strengthening the evidence base for future drought and water resource planning across the island.

Reexamining Chronic Toxoplasma gondii Infection: Surprising Activity for a “Dormant” Parasite - Anthony P. Sinai; Elizabeth A. Watts; Animesh Dhara; Robert D. Murphy; Matthew S. Gentry; Abhijit Patwardhan (Current Clinical Microbiology Reports, 2016)

Oxygen transport in periodically ventilated polychaete burrows - Elizabeth A. K. Murphy; Matthew A. Reidenbach (Marine Biology, 2016)

Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2016)

Homogenization and analysis of an expanded long‐term monthly rainfall network for the Island of Ireland (1850–2010) - S. Noone; C. Murphy; J. Coll; T. Matthews; D. Mullan; R. L. Wilby; S. Walsh (International Journal of Climatology, 2016)
Long‐term precipitation series are critical for understanding emerging changes to the hydrological cycle. To this end we construct a homogenized Island of Ireland Precipitation ( IIP ) network comprising 25 stations and a composite series covering the period 1850–2010, providing the second‐longest regional precipitation archive in the British‐Irish Isles. We expand the existing catalogue of long‐term precipitation records for the island by recovering archived data for an additional eight stations. Following bridging and updating of stations HOMogenisation softwarE in R ( HOMER ) homogenization software is used to detect breaks using pairwise and joint detection. A total of 25 breakpoints are detected across 14 stations, and the majority (20) are corroborated by metadata. Assessment of variability and change in homogenized and extended precipitation records reveal positive (winter) and negative (summer) trends. Trends in records covering the typical period of digitization (1941 onwards) are not always representative of longer records. Furthermore, trends in post‐homogenization series change magnitude and even direction at some stations. While cautionary flags are raised for some series, confidence in the derived network is high given attention paid to metadata, coherence of behaviour across the network and consistency of findings with other long‐term climatic series such as England and Wales precipitation. As far as we are aware, this work represents the first application of HOMER to a long‐term precipitation network and bodes well for use in other regions. It is expected that the homogenized IIP network will find wider utility in benchmarking and supporting climate services across the Island of Ireland, a sentinel location in the North Atlantic.

An evaluation of persistent meteorological drought using a homogeneous Island of Ireland precipitation network - R. L. Wilby; S. Noone; C. Murphy; T. Matthews; S. Harrigan; C. Broderick (International Journal of Climatology, 2016)
This paper investigates the spatial and temporal properties of persistent meteorological droughts using the homogeneous Island of Ireland Precipitation ( IIP ) network. Relative to a 1961–1990 baseline period it is shown that the longest observed run of below average precipitation since the 1850s lasted up to 5 years (10 half‐year seasons) at sites in southeast and east Ireland, or 3 years across the network as a whole. Dry spell and wet spell length distributions were represented by a first‐order Markov model which yields realistic runs of below average rainfall for individual sites and IIP series. This model shows that there is relatively high likelihood ( p = 0.125) of a 5‐year dry spell at Dublin, and that near unbroken dry runs of 10 years or more are conceivable. We suggest that the IIP network and attendant rainfall deficit modelling provide credible data for stress testing water supply and drought plans under extreme conditions.

A cyclone climatology of the British‐Irish Isles 1871–2012 - T. Matthews; C. Murphy; R. L. Wilby; S. Harrigan (International Journal of Climatology, 2016)
The British‐Irish Isles ( BI ) lie beneath the North Atlantic storm track year‐round and thus are impacted by the passage of extra‐tropical cyclones. Given recent extreme storminess and projections of enhanced winter cyclone activity for this region, there is much interest in assessing the extent to which the cyclone climate of the region may be changing. We address this by assessing a 142‐year (1871–2012) record of cyclone frequency, intensity and ‘storminess’ derived from the 20th Century Reanalysis V2 ( 20CR ) dataset. We also use this long‐term record to examine associations between cyclone activity and regional hydroclimate. Our results confirm the importance of cyclone frequency in driving seasonal precipitation totals which we find to be greatest during summer months. Cyclone frequency and storminess are characterized by pronounced interannual and multi‐decadal variability which are strongly coupled to atmospheric blocking in the Euro‐Atlantic region, but we detect no evidence of an increasing trend. We observe an upward trend in cyclone intensity for the BI region, which is strongest in winter and consistent with model projections, but promote caution interpreting this given the changing data quality in the 20CR over time. Nonetheless, we assert that long‐term reconstruction is helpful for contextualizing recent storminess and for identifying emerging changes in regional hydroclimate linked to cyclones.

Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

Ecological mechanisms underpinning climate adaptation services - Sandra Lavorel; Matthew J. Colloff; Sue Mcintyre; Michael D. Doherty; Helen T. Murphy; Daniel J. Metcalfe; Michael Dunlop; Richard J. Williams; Russell M. Wise; Kristen J. Williams (Global Change Biology, 2015)
Ecosystem services are typically valued for their immediate material or cultural benefits to human wellbeing, supported by regulating and supporting services. Under climate change, with more frequent stresses and novel shocks, 'climate adaptation services', are defined as the benefits to people from increased social ability to respond to change, provided by the capability of ecosystems to moderate and adapt to climate change and variability. They broaden the ecosystem services framework to assist decision makers in planning for an uncertain future with new choices and options. We present a generic framework for operationalising the adaptation services concept. Four steps guide the identification of intrinsic ecological mechanisms that facilitate the maintenance and emergence of ecosystem services during periods of change, and so materialise as adaptation services. We applied this framework for four contrasted Australian ecosystems. Comparative analyses enabled by the operational framework suggest that adaptation services that emerge during trajectories of ecological change are supported by common mechanisms: vegetation structural diversity, the role of keystone species or functional groups, response diversity and landscape connectivity, which underpin the persistence of function and the reassembly of ecological communities under severe climate change and variability. Such understanding should guide ecosystem management towards adaptation planning.

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Complex evolutionary history of the pallid dotted‐blue butterfly (Lycaenidae: Euphilotes pallescens ) in the Great Basin of western North America - Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; Chris C. Nice; James A. Fordyce; Matthew L. Forister (Journal of Biogeography, 2013)
Aim The aim of this study was to investigate patterns of genetic isolation associated with populations in discrete habitat patches in a North American cold desert through analysis of the pallid dotted‐blue butterfly, Euphilotes pallescens . This small butterfly is largely restricted to low‐elevation habitats across the Great Basin. The apparent geographical isolation and reported morphological variation among E. pallescens populations makes this species an ideal candidate with which to investigate patterns of genetic isolation and diversification in this arid region. Location Great Basin, western North America. Methods We used sequence data from nuclear and mitochondrial genes to investigate genetic diversity among E. pallescens populations, and among E. pallescens and a number of closely related Euphilotes species, using Bayesian phylogenetic analyses, as well as population genetic analyses. In conjunction with genetic variation, morphological variation was examined in the context of geographical and subspecific differentiation. Results Our genetic and morphological analyses suggest a moderate amount of isolation among populations, consistent with the hypothesis of restricted gene flow among isolated dune habitats, and possibly associated with isolation in distinct Pleistocene refugia. The patterns of diversification within E. pallescens and among closely related species are complicated by discordance among phylogenetic reconstructions based on nuclear and mitochondrial genes. Discordance among gene genealogies suggests a complex evolutionary history, perhaps involving alternating periods of reticulation and divergence in isolation. Main conclusions Although E. pallescens may be a vagile species, we find that persistence on isolated dunes in the Great Basin is associated with appreciable genetic and morphological differentiation among populations. However, genetic, morphological and taxonomic axes of variation are only partially in agreement. More generally, the discordance we find among genetic regions is consistent with the ascendant paradigm in phylogenetic reconstruction: gene genealogies often do not perfectly match species trees. Thus we present Euphilotes as a model for future biogeographical and phylogenetic reconstructions employing larger data sets of independent sequence markers.

Assessing Social Vulnerability to Climate Change in Human Communities near Public Forests and Grasslands: A Framework for Resource Managers and Planners - A. Paige Fischer; Travis Paveglio; Matthew Carroll; Daniel Murphy; Hannah Brenkert-Smith (Journal of Forestry, 2013)

Erratum to: The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Anne Battisti-Charbonney; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; et al. (Pflügers Archiv - European Journal of Physiology, 2013)

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; Joseph A. Fisher; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Climate model errors, feedbacks and forcings: a comparison of perturbed physics and multi-model ensembles - Matthew Collins; Ben B. B. Booth; B. Bhaskaran; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2011)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

Short-term antidepressant treatment modulates amygdala response to happy faces - Ray Norbury; Matthew J. Taylor; Sudhakar Selvaraj; Susannah E. Murphy; Catherine J. Harmer; Philip J. Cowen (Psychopharmacology, 2009)

Towards quantifying uncertainty in transient climate change - Matthew Collins; Ben B. B. Booth; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

Invertebrate hydraulic microhabitat and community structure in Callitriche stagnalis Scop. patches - Matthew T. Ó Hare; Kevin J. Murphy (Hydrobiologia, 1999)

Chromosomal localization of acidic and basic keratin genes of the domestic dog - Amy B. Miller; Matthew Breen; Keith E. Murphy (Mammalian Genome, 1999)